Exploring Science Curriculum Emphases in Relation to the Alberta Physics Program-of-Study - Chu, Man-Wai (Alberta Journal of Educational Research, 2012)
Using Roberts’ (1982, 1988, 1995, 1998, 2003) seven science curriculum emphases as its framework, this investigation into Alberta’s physics program-of-study found that pre-service and novice teachers reported focusing on four of the emphases—Structure of Science; Scientific Skill Development; Science, Technology, and Decisions; and Correct Explanation— while experienced teachers reported focusing on two of the emphases—Structure of Science and Everyday Coping. Other program-of-study aspects that were reported by teachers as being of high priority included holistic views of physics and student engagement, both of which fall beyond Roberts’ framework. Teacher participants focused on different aspects of the program-of-study as compared to a senior curriculum leader in Alberta (i.e., the program manager for secondary sciences in the Curriculum Branch of Alberta Education), suggesting a possible need for professional development for teachers to deliver the program-of-study as intended by Alberta Education. This research increases understanding of how teachers interpret a physics program-of-study with respect to science curriculum emphases. Reprenant comme cadre l'accent que met Roberts sur un programme d'études reposant sur sept priorités en sciences (1982, 1988, 1995, 1998, 2003), cette recherche du programme d'études en physique de l'Alberta a trouvé que les stagiaires et les enseignants débutants se concentraient sur quatre des priorités - La structure de la science; Le développement des habiletés en science; La science, la technologie et les décisions; et La bonne explication - alors que les enseignants plus expérimentés misaient deux des priorités - La structure de la science et Pour faire face au quotidien. Parmi d'autres aspects du programme d'études que les enseignants ont évoqués comme étant prioritaires notons des perspectives holistiques de la physique et l'implication des élèves, deux composantes qui ne sont pas inclues le cadre de Roberts. Les enseignants participants ont misé différents aspects du programme d'études par rapport au chef sénior du programme d'études (c'est-à-dire le gestionnaire de programme des sciences au secondaire de la Direction des programmes d'études de Alberta Education), ce qui donne à penser qu'il pourrait avoir un besoin de développement professionnel pour que les enseignants mettent en œuvre le programme d'études tel que prévu par Alberta Education. Cette recherche vient ajouter à nos connaissances sur l'interprétation que font les enseignants du programme d'études en physique relativement aux priorités en sciences.